Isolation, Characterization and Genomic Analysis of a Novel Jumbo Phage, AerS_266, That Infects Aeromonas salmonicida - Vera Morozova; Igor Babkin; Yuliya Kozlova; Artem Tikunov; Tatiana Ushakova; Alevtina Bardasheva; Valeria Fedorets; Elena Zhirakovskaya; Nina Tikunova (Microorganisms, 2023)
Aeromonas salmonicida is the causative agent of septicemia in fish, and it is associated with significant economic losses in the aquaculture industry. While piscine Aeromonas infections are mainly treated with antibiotics, the emergence of resistance in bacterial populations requires the development of alternative methods of treatment. The use of phages can be one of them. A novel A. salmonicida jumbo phage, AerS_266, was isolated and characterized. This phage infects only mesophilic A. salmonicida strains and demonstrates a slow lytic life cycle. Its genome contains 243,674 bp and 253 putative genes: 84 encode proteins with predicted functions, and 3 correspond to tRNAs. Genes encoding two multisubunit RNA polymerases, chimallin and PhuZ, were identified, and AerS_266 was thus defined as a phiKZ-like phage. While similar phages with genomes >200 kb specific to Aeromonas hydrophila and Aeromonas veronii have been previously described, AerS_266 is the first phiKZ-like phage found to infect A. salmonicida.